2015
DOI: 10.1074/jbc.m115.654798
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and in Vitro Evidence for Biochemical Coupling of Reactions Catalyzed by Lysophosphatidylcholine Acyltransferase and Diacylglycerol Acyltransferase

Abstract: Background: Plant polyunsaturated fatty acids (PUFAs) are mainly synthesized on phosphatidylcholine (PC). Results: Diacylglycerol acyltransferase (DGAT) produced higher amount of PUFA-containing TAG in the presence of acylCoA:lysophosphatidylcholine acyltransferase (LPCAT). Conclusion:The LPCAT-catalyzed reverse reaction can be coupled to the DGAT reaction for PUFA accumulation. Significance: A mechanism for enhancing the transfer of PUFAs from PC into TAG has been confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…These results are also consistent with recent coexpression and biochemical analyses using flax (Linum usitatissimum) DGAT1 and LPCAT (Pan et al, 2015). Those authors showed that LPCAT likely mediates the direct channeling of PC-derived acyl-CoA to DGAT1, thus accounting for the elevated polyunsaturated FA content in flax oil, while also helping to overcome the thermodynamically unfavorable reverse reaction of LPCAT (Pan et al, 2015). The results demonstrated here ( Fig.…”
Section: Atgpat9 Knockdown Seed Oil Phenotype and Protein Interactorsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are also consistent with recent coexpression and biochemical analyses using flax (Linum usitatissimum) DGAT1 and LPCAT (Pan et al, 2015). Those authors showed that LPCAT likely mediates the direct channeling of PC-derived acyl-CoA to DGAT1, thus accounting for the elevated polyunsaturated FA content in flax oil, while also helping to overcome the thermodynamically unfavorable reverse reaction of LPCAT (Pan et al, 2015). The results demonstrated here ( Fig.…”
Section: Atgpat9 Knockdown Seed Oil Phenotype and Protein Interactorsupporting
confidence: 81%
“…The homomeric and heteromeric interactions between AtGPAT9 and AtLPAAT2 or AtLPCAT2 were approximately 8-to 20-fold stronger than the corresponding interactions with AtDGAT1. Together, these results suggest that AtGPAT9 likely interacts in vivo with AtLPAAT2 (the next step in glycerolipid assembly after GPAT) and with AtLPCAT2, the main enzyme involved in acyl editing, which provides polyunsaturated FAs to the acyl-CoA pool for incorporation into de novo glycerolipid synthesis (Stymne and Stobart, 1984;Bates et al, , 2013bWang et al, 2012b;Lager et al, 2013;Pan et al, 2015).…”
Section: Atgpat9 Interacts Physically With Other Enzymes In the Kennementioning
confidence: 91%
“…The LPCATs in the microsomal fractions of C. sativa seeds showed a clear preference for 18C unsaturated acyl-CoA in the forward reaction. Similar substrate specificity of the LPCATs in the microsomal fractions of yeast with mutated main endogenous acyl-CoA:lysophospholipid acyltransferase (ALE1) overexpressed with genes encoding the LPCATs of A. thaliana, L. fendleri, C. tinctorius, R. communis, H. benghalensis and L. usitatissimum were previously shown (Lager et al 2013;Pan et al 2015). Thus, it seems that the LPCATs in oilseed plants do not discriminate between 18:2-CoA and 18:3-CoA in favour of 18:1-CoA.…”
Section: Discussionsupporting
confidence: 60%
“…It has been postulated since the 1980s that LPCATs play a role in acyl exchange between PC and the acyl-CoA pool via the backward reaction (Stymne and Glad 1981;Stymne and Stobart 1984). However, the fact that LPCATs can operate in both the forward and backward directions has been definitively proven only recently (Lager et al 2013;Pan et al 2015;Jasieniecka-Gazarkiewicz et al 2016). To date, the capacity of the backward reactions of LPCATs in the developing seeds of oilseed plants has not been specified; therefore, it was not possible to establish to what extent they could be responsible for the transfer of polyunsaturated fatty acids from PC to the acyl-CoA pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation